The Relationship of Family Support and Medication Adherence on Recurrence of Patients with Auditory Hallucination - Perdana, Risky Kurnia; Wijaya, I Kade; Sia’tang, Weni (Bantayang Omni Cendekia, 2024)
Background: Recurrence of auditory hallucinations refers to the reappearance of signs and symptoms of a disease after an adverse event. Recurrence is influenced by several factors, including lack of family support and poor medication adherence. Objective: This study aimed to examine the relationship of family support and medication adherence with on recurrence of auditory hallucination sufferers at the Jongaya Health Center Makassar. Methods: This study utilized a correlational design with a cross-sectional study approach. The sampling technique in this study employed total sampling, which included 34 respondents. Results: The Chi-Square test showed that there was a relationship between family support and recurrence of auditory hallucination sufferers (p-value= 0.001) and there was a relationship between medication adherence and recurrence of auditory hallucination sufferers (p-value= 0.007). Conclusion: There is a relationship of family support and medication adherence on the recurrence of auditory hallucination sufferers at Jongaya Health Center Makassar. Thus, it is expected to increase family knowledge regarding the importance of family support to prevent the auditory hallucination recurrence.